2016
DOI: 10.1371/journal.pone.0151601
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Erythroferrone and Biomarkers of Erythropoiesis and Iron Metabolism, and Treatment with Long-Term Erythropoiesis-Stimulating Agents in Patients on Hemodialysis

Abstract: BackgroundWe aimed to identify associations between erythroferrone (ERFE), a regulator of hepcidin 25, and biomarkers of erythropoiesis and iron metabolism. We also aimed to determine the effects of erythropoiesis-stimulating agents (ESA), continuous erythropoietin receptor activator (CERA) and darbepoetin-α (DA) on ERFE production in patients on hemodialysis (HD).MethodsBlood samples were obtained from 59 patients before HD sessions on day 0 (baseline). Twenty patients who were injected with either CERA (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 16 publications
5
59
2
1
Order By: Relevance
“…The absence of a correlation between ERFE and hepcidin plasma levels in our study differs from a previous report on associations between both analytes that were observed using the same FAM132B ELISA in a study among hemodialysed patients 3. However, our observations on lack of correlations of ERFE plasma levels and plasma hepcidin and EPO levels are in agreement with those obtained in a study among patients with chronic mountain sickness (as defined by excessive erythrocytosis, hemoglobin ≥ 21 g/dL, and hypoxemia with no other medical explanation), who underwent isovolemic venesection of 500 mL on four consecutive days (days 1‐4) 6.…”
Section: Tablecontrasting
confidence: 99%
See 2 more Smart Citations
“…The absence of a correlation between ERFE and hepcidin plasma levels in our study differs from a previous report on associations between both analytes that were observed using the same FAM132B ELISA in a study among hemodialysed patients 3. However, our observations on lack of correlations of ERFE plasma levels and plasma hepcidin and EPO levels are in agreement with those obtained in a study among patients with chronic mountain sickness (as defined by excessive erythrocytosis, hemoglobin ≥ 21 g/dL, and hypoxemia with no other medical explanation), who underwent isovolemic venesection of 500 mL on four consecutive days (days 1‐4) 6.…”
Section: Tablecontrasting
confidence: 99%
“…Correlations were found between levels of ERFE and hepcidin, ferritin, and soluble transferrin receptor (sTfR) 3. In the present study we aim to validate this kit by measurement of ERFE in β‐thalassemia intermedia patients and in healthy blood donors before and after blood donation and to correlate findings with other markers of erythropoiesis and iron metabolism.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Honda et al examined the association between ERFE and biomarkers of iron metabolism in haemodialysis patients and found that levels of ERFE were inversely correlated with levels of hepcidin and ferritin and positively correlated with soluble transferrin receptor. They also showed that the use of ESAs increased the levels of ERFE that regulated hepcidin and led to iron mobilisation from body stores during erythropoiesis (30). Additional studies of this pathway and its potential effects in CKD are warranted.…”
Section: Erythropoiesismentioning
confidence: 99%
“…It is likely that increased erythroblasts in the dyserythropoietic bone marrow secrete a factor that inhibits hepcidin expression. In mice, erythroferrone (FAM132b), a tumor necrosis factor superfamily molecule, was shown to be expressed by erythroblasts and suppress hepcidin expression [54][55][56][57][58].…”
Section: Regulation Of Systemic Iron Homeostasis By Hepcidinmentioning
confidence: 99%